Levels of Graphical Comprehension in Statistical Activities in Mathematics Textbooks - Camila Peralta; Nicolás Sánchez-Acevedo (EDUPEDIA PUBLISHER, 2026)
Purpose: The development of statistical competence is a central objective in contemporary education, enabling students to interpret and critically engage with data in everyday contexts. Graphical comprehension—defined as the ability to read, interpret, and analyse statistical representations—constitutes a key curricular skill. This study examines the levels of graphical comprehension promoted by statistical graph activities in mathematics textbooks distributed by the Chilean Ministry of Education for Year 7 (ages 12–13) to Year 10 (ages 15–16). Methodology: A qualitative descriptive design was employed, using content analysis to systematically examine textbook activities involving statistical graphs. The analysis was guided by Aoyama’s hierarchy of graphical comprehension to classify the cognitive demand of tasks. Findings: The results reveal a strong predominance of Level 2 activities, focused on basic graph reading, including the identification of explicit values and simple comparisons. The proportion of such tasks increases from 67.7% in Year 7 to 90% in Year 10, indicating a decline in cognitive demand across grade levels. Higher-order levels—rational/literal (Level 3) and critical (Level 4)—are minimally represented, while hypothesis generation (Level 5) is entirely absent. Significance: These findings suggest that current textbooks predominantly emphasise lower-order cognitive skills, thereby limiting the development of advanced analytical and critical reasoning in statistics. The study highlights the need to redesign textbook activities to progressively foster higher levels of graphical comprehension, with implications for both pre-service and in-service teacher education.